2011
DOI: 10.1021/ac200771g
|View full text |Cite
|
Sign up to set email alerts
|

Relative Quantification of Phospholipid Accumulation in the PC12 Cell Plasma Membrane Following Phospholipid Incubation Using TOF-SIMS Imaging

Abstract: Time of flight secondary ion mass spectrometry (TOF-SIMS) imaging has been used to investigate the incorporation of phospholipids into the plasma membrane of PC12 cells after incubation with phosphatidylcholine (PC) and phosphatidylethanolamine (PE). The incubations were done at concentrations previously shown to change the rate of exocytosis in model cell lines. The use of TOF-SIMS in combination with an in situ freeze fracture device enables the acquisition of ion images from the plasma membrane in single PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 33 publications
0
37
0
Order By: Relevance
“…By expanding upon relative quantitative methods developed in the SIMS community, 40,74,75 a deuterium labeling scheme has been reported to estimate the amount of lipid that was incorporated into these augmented secretory cells. 76 The method used the same incubation procedure and cell line used in several of the studies described here 62,75,77 but substituted the exogenous lipids for lipids with deuterated acyl chains. The deuterium label supplied a unique peak that was used to track the relative amount of the added lipid.…”
Section: ■ Fundamental Ims Based Applications In Neurosciencementioning
confidence: 99%
See 1 more Smart Citation
“…By expanding upon relative quantitative methods developed in the SIMS community, 40,74,75 a deuterium labeling scheme has been reported to estimate the amount of lipid that was incorporated into these augmented secretory cells. 76 The method used the same incubation procedure and cell line used in several of the studies described here 62,75,77 but substituted the exogenous lipids for lipids with deuterated acyl chains. The deuterium label supplied a unique peak that was used to track the relative amount of the added lipid.…”
Section: ■ Fundamental Ims Based Applications In Neurosciencementioning
confidence: 99%
“…The results suggest that the observed changes in exocytosis were brought about by very small changes (0.5−1.3%) in lipid composition. 76 The implication is that subtle lipid heterogeneity across the membrane of a cell could be a powerful regulatory mechanism for these events. Indeed, events measured at these cells are fairly heterogeneous and work has shown that locations on a single cell can be more active, so-called hot spots.…”
Section: ■ Fundamental Ims Based Applications In Neurosciencementioning
confidence: 99%
“…Mammalian cardiac tissue and individual isolated cardiac cells have been imaged to visualize both tissue-level and subcellular localization of phosphocholine and other lipids such as cardiolipins, revealing complimentary distributions and correlating them with particular fatty acids [73]. Lanekoff et al [80] used a stable-isotope labeling approach to determine membrane lipid exchange rates in PC12 cells by imaging the membrane to trace deuterated phospholipids that were incorporated into the cells from culture medium at various time points. Low rates of exchange were observed, leading the authors to conclude that small membrane compositional changes may result in large changes in cellular activity, e.g., exocytosis, as observed in their previous work with a comparable cell treatment [81].…”
Section: Secondary Ion Mass Spectrometry (Sims)mentioning
confidence: 99%
“…For relative quantitation of specific metabolites, as in the case of bacteria, incorporation of stable isotope label nutrients into the mammalian cell and subcellular structures can be tracked using SIMS. The Ewing group [41] recently employed this approach to measure the accumulation of extracellular membrane phospholipids into pheochromocytoma PC12 cell membranes as a function of the environmental concentrations of phospholipids. PC12 cells were cultured in medium enriched with deuterated membrane phospholipids—either phosphatidylcholine (PC) or phosphatidylethanolamine (PE)— and then the cells were freeze-fractured; those with exposed outer membranes were imaged by SIMS.…”
Section: Animalsmentioning
confidence: 99%